Progress in the application of ultrasound in glioma surgery - Wu, Hao; Cheng, Yingying; Gao, Wenwen; Chen, Peng; Wei, Yao; Zhao, Haikang; Wang, Fenglu (Frontiers in Medicine, 2024)
Brain glioma is the most common primary intracranial tumor, which is highly invasive and has a poor prognosis. Maximum safe tumor removal is now recognized as the gold standard for glioma surgery. The application of intraoperative ultrasound can improve the tumor resection rate and protect the brain function area to the maximum extent. At present, a variety of new imaging techniques have been applied in the clinical practice of intraoperative ultrasound, including contrast-enhanced ultrasound, three-dimensional ultrasound, ultrasound elastography and linear ultrasound, which can assist the surgeon to perform tumor resection. This article will review the role and deficiency of intraoperative ultrasound in glioma surgery.